Community based e-Museum framework: towards sustainable cultural heritage information system / Suriyati Razali - Razali, Suriyati (Institute of Graduate Studies, UiTM, 2012)
This research presents the work that conceptualizes a new phenomenon of sharing cultural knowledge through a model of an E-museum which is coined as the community based E-museum. This conceptualization is motivated by two main factors. The first factor is the growing need for museums to manage the digitization of their museum artifacts while trying to re ach out for more historical or cultural artifacts whose custodians are individuals or families who are reluctant to surrender their artifacts to museums. The second factor is the rapid growth of user generated content that thrives on the simplicity but powerful web technology which signifies the willingness of users to participate in the contribution of content in the online social media. To gain a better understanding of museums’ functions and processes, an extensive literature review was done to trace the development of the new museology and trend of e-museums was made. This community based E-museum (ComE) model is conceptualized against a backdrop that illustrates the e-museum evolution against a technology trend that managed to engage users in active online participation in the virtual world. The ComE is conceptualized as an E-museum that empowers community members who are owners of cultural artifacts to share the artifacts with other e-museum visitors through the curatorship of digital forms of the artifacts while maintaining the custodianship of the artifact.